Near-field blast vibration monitoring and analysis for prediction of blast damage in sublevel open stoping - Fleetwood, Kelly Gene (Curtin University, 2010)
The work presented in this thesis investigates near-field blast vibration monitoring, analysis, interpretation and blast damage prediction in sublevel open stoping geometries. As part of the investigation, seven stopes at two Australian sublevel open stoping mines were used as case studies. The seven stopes represented significant ranges in stope shapes, sizes, geotechnical concerns, extraction sequences, stress conditions, blasting geometries and rock mass properties.The blast damage investigations at the two mine sites had three main components. The first component was rock mass characterisation, which was performed using static intact rock testing results, discontinuity mapping, mining-induced static stress modelling and geophysical wave propagation approaches. The rock mass characterisation techniques identified localised and large-scale variations in rock mass properties and wave propagation behaviours in relation to specified monitoring orientations and mining areas. The other components of the blast damage investigations were blast vibration monitoring and analysis of production blasting in the seven stopes and stope performance assessments.The mine-based data collection period for the case studies lasted from January, 2006 to February, 2008. A key element of the data collection program was near-field blast vibration monitoring of production blasts within the seven study stopes. The instrumentation program consisted of 41 tri-axial accelerometers and geophone sondes, installed at distances from 4m to 16m from the stope perimeters. A total of 59 production firings were monitored over the course of the blast vibration monitoring program. The monitoring program resulted in a data set of over 5000 single-hole blast vibration waveforms, representing two different blasthole diameters (89mm and 102mm), six different explosive formulations and a wide range in charge weights, source to sensor distances, blasthole orientations and blasting geometries.The data collected in the blast vibration monitoring program were used to compare various near-field charge weight scaling relationships such as Scaled Distance and Holmberg-Persson prediction models. The results of these analyses identified that no single charge weight scaling model could dependably predict the measured near-field peak amplitudes for complex blasting geometries. Therefore, the general form of the charge weight scaling relationship was adopted in conjunction with nonlinear multivariable estimation techniques to analyse the data collected in the study stopes and to perform forward vibration predictions for the case studies.Observed variations in the recorded near-field waveforms identified that instantaneous peak amplitude such as peak particle velocity (PPV) did not accurately describe the characteristics of a large portion of the data. This was due to significant variations in frequency spectra, variable distributions of energy throughout the wave durations and coupling of wave types (e.g. P- and S-wave coupling). The wave properties that have been proposed to more accurately characterise complex nearfield vibrations are the total wave energy density (ED[subscript]W-tot), stored strain energy density (ED[subscript]W-SS) and the wave-induced mean normal dynamic strain (ε[subscript]W-MN). These wave properties consider the activity of the blast-induce wave at a point in the rock mass over the entire duration instead of the instantaneous amplitude.A new analytical approach has been proposed to predict blast-induced rock mass damage using rock mass characterisation data, blast vibration monitoring results and rock fracture criteria. The two-component approach separately predicts the extent of blast-induced damage through fresh fracturing of intact rock and the extent from discontinuity extension. Two separate damage criteria are proposed for the intact rock portion of the rock mass based on tensile and compressive fracture strain energy densities and compressive and tensile fracture strains. The single criterion for extension of existing discontinuities is based on the required fracture energy density to activate all macro-fractures in a unit volume of the rock mass.The proposed energy-based criteria for intact rock fracture and extension of discontinuities integrate strain rate effects in relation to material strength. The strainbased criterion for intact rock fracture integrates the existing mining-induced static strain magnitudes. These factors have not been explicitly considered in existing empirical or analytical blast damage prediction models. The proposed blast damage prediction approach has been applied to two stopes during the two mine site case studies.